2017
DOI: 10.1186/s40405-017-0025-4
|View full text |Cite
|
Sign up to set email alerts
|

Why do young adults gamble online? A qualitative study of motivations to transition from social casino games to online gambling

Abstract: The present research examined the mechanisms of initiating online gambling among young adults. Of particular interest was whether social casino gaming was noted as part of young adults’ experience with online gambling. This is because there is growing concern that social casino gaming may be a ‘gateway’ to online gambling. Three focus groups (N = 21) were conducted with young adult online gamblers from two large Canadian Universities. Participants noted the role of peer influence as well as incentives (e.g., s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 26 publications
0
17
0
4
Order By: Relevance
“…Gambling Marketing Perceptions Perceptions of gambling marketing seem, overall, quite negative and are often worse for active gamblers than for the general population [33,36,40]. Children also report being influenced by gambling marketing, such as financial incentives to gamble and odds advertising [14,20,41], for instance misperceiving marketing about financial incentives to mean that gamblers could never lose [42,43]. However, there are also limitations inherent to any type of self-report data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gambling Marketing Perceptions Perceptions of gambling marketing seem, overall, quite negative and are often worse for active gamblers than for the general population [33,36,40]. Children also report being influenced by gambling marketing, such as financial incentives to gamble and odds advertising [14,20,41], for instance misperceiving marketing about financial incentives to mean that gamblers could never lose [42,43]. However, there are also limitations inherent to any type of self-report data.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, the nascent literature on this topic has relied on self-reports, which provide useful insight but are based on the fallibilities of memory. One qualitative study of young people in Canada found that social casino games were an entry point to online gambling, and that advertising in these games served as an entry point to other forms of online gambling [20]. Australian youths have also been found to be exposed to social casino advertising [21].…”
Section: Gambling Marketing Content and Frequencymentioning
confidence: 99%
See 1 more Smart Citation
“…Gambling activities can provide individuals with many subjective benefits, such as excitement, entertainment, and a perceived sense of acquiring wealth without much effort (Derevensky and Gilbeau 2015 ; Kim et al 2017 ). However, both recreational and problematic gambling alike are associated with several psychosocial, physical, and mental health problems (Fröberg et al 2015 ; Kong et al 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, other forms of 'earning money' among young people, e.g. poker, are observed (DiCicco-Bloom & Romer, 2012;Kim, Wohl, Gupta, & Derevensky, 2017). That is why, it is worth examining the level of an investment activity among the last semester master's degree students of economics fields as the potential active participants of financial markets, including an investment in stocks and an investment in forex in comparison to a poker game.…”
Section: Introductionmentioning
confidence: 99%